THE EFFECT OF WORK AUTONOMY ON WORK LIFE BALANCE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATION VARIABLE - Mursidi, Mursidi; Khasanah, Kurnia Wardatul (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The paradigm of working women brings a consistency of dual roles that will be carried out between responsibilities at home and responsibilities at work in the office. Researchers make working women as subjects in this study, especially female teachers. This is because with high job demands, it will be difficult to commit, which in turn has an impact on the difficulty of achieving a work-family balance. Nevertheless, teachers have high work autonomy so it is possible to achieve work-life balance. The research respondents were female teachers of all Muhammadiyah Vocational Schools in Lumajang Regency, the data obtained was then analyzed using SmartPLS. The result of the research is that work autonomy has a positive and significant effect on work-life balance, organizational commitment has a positive and significant effect on work-life balance and work-life balance has a positive and significant effect. Organizational commitment is able to mediate work autonomy on work-life balance in teachers, which means that organizational commitment succeeds in mediating work autonomy in a positive and significant way on work-life balance in Muhammadiyah school teachers in Lumajang.